Optimization of regeneration process of spent bleaching earth. Issue 1 (June 2020) - Pranowo, D; Dewanti, B S D; Fatimah, H; Setyawan, H Y
Abstract: The bleaching process is critical to improving the colour, flavour, taste, and stability of the final oil products of palm oil. The bleaching process uses bleaching earth (BE), which after several cycles, becomes a waste called Spent Bleaching Earth (SBE). Impurities cover the surface of SBE from the purification process. Regeneration by utilizing acid can increase the absorption capacity of SBE. The purpose of this research is to obtain the optimal combination of nitric acid concentration and heating temperature in the regeneration process of SBE. Response Surface Method (RSM) with Central Composite Design (CCD) was employed, using two factors of concentration of nitric acid and the heating temperature. The responses analysed in this research include colour, absorption efficiency, and yield. The obtained optimum condition in the treatment was found in the concentration of nitric acid (0.75 M) and a heating temperature of 430.8°C. The results of this research indicated colour absorption efficiency of 95.7557%, the yield of 52.4846%. The verified optimal solution obtained was 94.68% of absorption efficiency and 51.43% of yield. The Regenerated Spent Bleaching Earth (RSBE) optimum conditions compared to BE. The colour absorption efficiency utilizing BE was 96.77%, 2% higher than that of RSBE at 94.68%. The value of RSBE colour absorption efficiency in optimum conditions similar to that of the BE.